Curcumin suppresses cell proliferation and triggers apoptosis in vemurafenib‐resistant melanoma cells by downregulating the EGFR signaling pathway - Chiu, Yu‐Jen; Yang, Jai‐Sing; Tsai, Fuu‐Jen; Chiu, Hong‐Yi; Juan, Yu‐Ning; Lo, Yu‐Hsiang; Chiang, Jo‐Hua (Environmental toxicology, 2022)
Melanoma is a malignant tumor with aggressive behavior. Vemurafenib, a BRAF inhibitor, is clinically used in melanoma, but resistance to melanoma cytotoxic therapies is associated with BRAF mutations. Curcumin can effectively inhibit numerous types of cancers. However, there are no reports regarding the correlation between curcumin and vemurafenib‐resistant melanoma cells. In this study, vemurafenib‐resistant A375.S2 (A375.S2/VR) cells were established, and the functional mechanism of the epidermal growth factor receptor (EGFR), serine–threonine kinase (AKT), and the extracellular signal‐regulated kinase (ERK) signaling induced by curcumin was investigated in A375.S2/VR cells in vitro. Our results indicated that A375.S2/VR cells had a higher IC50 concentration of vemurafenib than the parental A375.S2 cells. Moreover, curcumin reduced the viability and confluence of A375.S2/VR cells. Curcumin triggered apoptosis via reactive oxygen species (ROS) production, disruption of mitochondrial membrane potential (ΔΨm), and intrinsic signaling (caspase‐9/‐3‐dependent) pathways in A375.S2/VR cells. Curcumin‐induced apoptosis was also mediated by the EGFR signaling pathway. Combination treatment with curcumin and gefitinib (an EGFR inhibitor) synergistically potentiated the inhibitory effect of cell viability in A375.S2/VR cells. The present study provides new insights into the therapy of vemurafenib‐resistant melanoma and suggests that curcumin might be an encouraging therapeutic candidate for its drug‐resistant treatment.